SEX RATIO OF CERTAIN SPECIES OF LOCUST LARVAE OF KARACHAY-CHERKESSIA - Zukhra S. Temirlieva (Юг России: экология, развитие, 2017)
Aim. The aim of the work is to determine the sex ratio of the larvae of some locust species of the Karachay-Cherkess Republic (2014-2015). Materials and methods. Data on the ratio of the sexes of the studied locust species (Omocestus haemorrhoidalis Ch., Chorthippus albomarginatus Deg., Chorthippus bigutullus L., Chorthippus apricarius L., Chorthippus mollis Ch.) was obtained by observing the hatching of larvae in the cage in natural conditions in 4 regions of Karachay-Cherkessia. Traditional methods for catching and registering locusts were used in the work. Results. Studies have shown the predominance of females for all model species. In some cases, 2-4 larvae emerged from one egg. The duration of the age varies within a few days but the fertility of female species can vary significantly depending on the impact of environmental factors. These studies confirm the fact of the change in the number of eggs in locust pods depending on the breadth of habitat. Conclusion. Information on the timing of the emergence and development of dominant species, their fertility, etc. can be used by the plant protection service for an objective assessment of the state of a population of harmful species and forecasting their abundance in the region.